Practitioners' experiences of the mental capacity act: a systematic review. Issue 4 (15th September 2020) - Scott, Jade; Weatherhead, Stephen; Daker-White, Gavin; Manthorpe, Jill; Mawson, Marsha
Abstract : Purpose: The Mental Capacity Act (MCA, 2005) provided a new legal framework for decision-making practice in England and Wales. This study aims to explore qualitative research on practitioners' knowledge and experiences of the MCA in health and social care settings to inform practice and policy. Design/methodology/approach: Four electronic databases and Google Scholar were searched in November 2019 for peer-reviewed, qualitative, English language studies exploring practitioners' experiences and knowledge of the MCA in health and social care settings. Nine studies were included and appraised for methodological quality. Data were analysed using thematic synthesis. Findings: Data revealed both positive aspects and challenges of applying the MCA in practice within five main themes, namely, travelling the "grey line", the empowering nature of the MCA, doing the assessment justice, behaviours and emotional impact and knowledge gaps and confidence. Practical implications: The fundamental principles of the MCA appear to be adhered to and embedded in practice. However, practitioners find mental capacity work remains challenging in its uncertainties. While calling for more training, they may also benefit from further MCA skills development and support to increase confidence and reduce apprehension. Originality/value: This is the first systematic review to synthesise qualitative literature on practitioners' experiences and knowledge of the MCA. Findings offer insight into practice experiences of the MCA and provide a basis for the development of training and supervisory support.